2013
DOI: 10.1017/s1461145713001090
|View full text |Cite
|
Sign up to set email alerts
|

Genetic approaches to understanding post-traumatic stress disorder

Abstract: Post-traumatic stress disorder (PTSD) is increasingly recognized as both a disorder of enormous mental health and societal burden, but also as an anxiety disorder that may be particularly understandable from a scientific perspective. Specifically, PTSD can be conceptualized as a disorder of fear and stress dysregulation, and the neural circuitry underlying these pathways in both animals and humans are becoming increasingly well understood. Furthermore, PTSD is the only disorder in psychiatry in which the initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 184 publications
0
77
0
8
Order By: Relevance
“…Candidate gene studies, in which genes are selected for study based on biological pathways thought to have a role in PTSD, have identified a number of genes possibly associated with risk of PTSD. These include genes involved in the hypothalamicpituitary-adrenal (HPA) axis, the noradrenergic, serotonergic and dopaminergic systems, memory consolidation, and other biological systems (Almli et al, 2014;Logue et al, 2015). However, some of these candidate gene studies have failed to replicate.…”
Section: Targeting Interventionsmentioning
confidence: 99%
“…Candidate gene studies, in which genes are selected for study based on biological pathways thought to have a role in PTSD, have identified a number of genes possibly associated with risk of PTSD. These include genes involved in the hypothalamicpituitary-adrenal (HPA) axis, the noradrenergic, serotonergic and dopaminergic systems, memory consolidation, and other biological systems (Almli et al, 2014;Logue et al, 2015). However, some of these candidate gene studies have failed to replicate.…”
Section: Targeting Interventionsmentioning
confidence: 99%
“…Until recently, the genetic contribution to PTSD has been investigated largely via candidate gene association studies (reviewed in Almli et al, 2014;Amstadter et al, 2009;Norrholm and Ressler, 2009). Most research has focused on: (1) the hypothalamic-pituitary-adrenal (HPA) axis, (2) the ascending brainstem locus coeruleus noradrenergic system, and (3) the limbic amygdalar frontal pathway mediating fear processing.…”
Section: Introductionmentioning
confidence: 99%
“…Candidate studies of PTSD have identified > 50 genes that exert significant effects (for reviews, see [22, 23]), with some finding a significant effect of the Val66Met BDNF polymorphism on PTSD [24]. This polymorphism is functional, as the Met allele is associated with reduced BDNF gene expression [25], impeding the extinction of conditioned fear [26].…”
Section: Introductionmentioning
confidence: 99%